Fully-spliced HIV-1 RNAs are reverse transcribed with similar efficiencies as the genomic RNA in virions and cells, but more efficiently in AZT-treated cells - Houzet, Laurent (BioMed Central, 2007)
We have shown previously that HIV actively and selectively packages the spliced HIV RNAs into progeny virions. In the present study, by using a RT-QPCR and QPCR strategies, we show that spliced viral RNAs are present in infectious particles and consequently participate, along with the unspliced genomic RNA, to some of the early steps of infection such as the reverse transcription step. This work provides the first quantitative data on reverse transcription of the fully spliced viral RNAs, also called the early transcripts, in target cells but also inside virions. The latter results were obtained by measuring the natural endogenous reverse transcription activity directly on intact HIV-1 particles. Our study reveals that spliced HIV RNAs are reverse transcribed as efficiently as the genomic RNA, both in cells and virions. Interestingly, we also show that reverse transcription of spliced RNAs is 56-fold less sensitive to the inhibitor AZT than reverse transcription of the genomic RNA. Therefore, the selection mediated by inhibitors of reverse transcription used to treat patients could lead to increased representativeness of spliced forms of HIV, thus favoring recombination between the HIV DNA species and facilitating HIV recovery.